2019
DOI: 10.3390/rs11141690
|View full text |Cite
|
Sign up to set email alerts
|

The Precipitation Structure of the Mediterranean Tropical-Like Cyclone Numa: Analysis of GPM Observations and Numerical Weather Prediction Model Simulations

Abstract: This study shows how satellite-based passive and active microwave (MW) sensors can be used in conjunction with high-resolution Numerical Weather Prediction (NWP) simulations to provide insights of the precipitation structure of the tropical-like cyclone (TLC) Numa, which occurred on 15-19 November 2017. The goal of the paper is to characterize and monitor the precipitation at the different stages of its evolution from development to TLC phase, throughout the storm transition over the Mediterranean Sea. Observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 58 publications
(64 reference statements)
2
34
2
1
Order By: Relevance
“…MERRA-2 maximum values could be mainly found in the mainland of Greece and Italy in comparison with that of modeled and remote sensing that were also observed in the Adriatic Sea. The same result was evident in a relevant modeling study of cyclone Numa, also supported by radar data [37]. Concerning cyclone Zorbas, the accumulated precipitation fields derived from the satellite estimates tended to extreme rainfall values in the South Mediterranean (Figure 17).…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…MERRA-2 maximum values could be mainly found in the mainland of Greece and Italy in comparison with that of modeled and remote sensing that were also observed in the Adriatic Sea. The same result was evident in a relevant modeling study of cyclone Numa, also supported by radar data [37]. Concerning cyclone Zorbas, the accumulated precipitation fields derived from the satellite estimates tended to extreme rainfall values in the South Mediterranean (Figure 17).…”
Section: Resultssupporting
confidence: 80%
“…Differences in the maximum values were evident in the range of 4 to 5 m/s and could be found in the cyclones Trixi and Zorbas. It should also be stated that maximum wind speed results in cyclone Numa are in good agreement with the ones presented in a similar study for the same event [37]. The resulting significant wave heights from the different runs were evaluated against the ones derived from JASON satellites.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Previous studies have shown that DC is weaker or shallower during and after the maximum intensity of some MTLCs (e.g. Claud et al, 2010;Miglietta et al, 2013;Cioni et al, 2016;Marra et al, 2019) but this statement was not confirmed for the majority of the selected MTLCs presented in this study. In addition, the DC during NUMA followed the diurnal solar cycle, probably due to the radiative cooling of the cloud tops, a process that increases instability in the troposphere (Wu and Ruan, 2016), but additional analysis has to be conducted to investigate this feature.…”
Section: Summary and Future Workcontrasting
confidence: 90%
“…The first one between 1200 UTC 17 November and 0600 UTC 18 November 2017 was directly associated with an MCS in the upshear left quadrant which was detected by numerous DCPIXELS (Figure 9h) and COV for more than 12 hr when DLS was weaker or slightly stronger than 10 m⋅s −1 and the vortex tilt was less than 50 km (Figure 8h). Also during this period, the maximum intensity of the cyclone was estimated by ERA5 as for Marra et al (2019). The DC activity was clearly closer to the centre compared to the first 12 hr of the tracking, even though MWDC and COV were detected in the outer parts of the cyclone periphery (e.g.…”
Section: Influences Of Deep Convection and Wind Shear On The Cyclone mentioning
confidence: 91%